2019
DOI: 10.1016/j.jembe.2019.151208
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and light-dependent proton pumps increase boundary layer pH in tropical macroalgae: A proposed mechanism to sustain calcification under ocean acidification

Abstract: Ocean acidification (OA) projections predict ocean pH to decline between 0.2 and 0.4 by 2100 with potential negative consequences for marine calcifiers without acclimation or adaption strategies to accomodate greater [H + ] in seawater. Biotic control of calcified reef macroalgae thalli surface diffusive boundary layer (DBL) chemistry may overcome low pH in seawater as one strategy to accommodate OA conditions. To investigate this strategy, we examined surface DBL O 2 and pH dynamics in five calcifying macroal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 66 publications
3
21
0
Order By: Relevance
“…Also, comparisons among different species, from the same habitat, suggest a variability in the strength of the coupling between photosynthesis and calcification (Vaśquez-Elizondo and Enrıquez, 2016;Qui-Minet et al, 2021). The direct relationship between these processes was demonstrated early on (Digby, 1977;Pentecost, 1978;Borowitzka, 1981;Borowitzka, 1987) and is supported by recent studies (e.g., Martin et al, 2013;Vaśquez-Elizondo and Enrıquez, 2016;Sordo et al, 2019), which showed a decline in calcification upon inhibition of photosynthesis (Hofmann et al, 2016;McNicholl et al, 2019). This link has been related to an elevation of the pH at the calcification site due to photosynthetic activity.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Also, comparisons among different species, from the same habitat, suggest a variability in the strength of the coupling between photosynthesis and calcification (Vaśquez-Elizondo and Enrıquez, 2016;Qui-Minet et al, 2021). The direct relationship between these processes was demonstrated early on (Digby, 1977;Pentecost, 1978;Borowitzka, 1981;Borowitzka, 1987) and is supported by recent studies (e.g., Martin et al, 2013;Vaśquez-Elizondo and Enrıquez, 2016;Sordo et al, 2019), which showed a decline in calcification upon inhibition of photosynthesis (Hofmann et al, 2016;McNicholl et al, 2019). This link has been related to an elevation of the pH at the calcification site due to photosynthetic activity.…”
Section: Introductionmentioning
confidence: 72%
“…It has been suggested that calcification is a biologically induced, rather than a controlled process, associated with cell wall organic-matrixinduced mineralization (Nash et al, 2019). However, mechanistic studies and derived models suggest that coralline algae exert some control over the calcification process, by promoting favorable conditions for CaCO 3 precipitation through photosynthesis and active dissolved inorganic carbon (DIC) and ion transport pathways (Comeau et al, 2013;Koch et al, 2013;Hofmann et al, 2016;Cornwall et al, 2017;McNicholl et al, 2019). Recent studies showed that the extent of photosynthesis-promoted increase of pH in the DBL (pH DBL ) is species-specific and influenced by external seawater pH, but also by species' morphology, due to its strong influence on DBL thickness (Cornwall et al, 2017;Schubert et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Although calcification is correlated to photosynthesis, there are also metabolically controlled photosynthesis-independent ion pumps and channels with the efflux of Ca 2+ and H + outside the cells in the dark and influx under light (Hofmann et al ., 2016). The proton pumps in light are important to pH regulation at the thalli surface and calcification under ocean acidification (McNicholl et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of algal biomass can result in self-shading, therefore, leading to reduced levels of photosynthetically active radiation (PAR) and/ or altered exposures of changed light spectrum to the cells due to differences in primary and secondary absorption (re-absorbtion of the attenuated light by other cells). On the other hand, water motion dynamics in aerated, mixed or shaken cultures can affect the thickness of diffusion boundary layers (DBL) surrounding cells or individuals; therefore, different levels of water motion or current can result in different levels of pH, pCO 2 , and pO 2 near the cell or thallus surface compared to the bulk medium (Hurd 2015;McNicholl et al 2019). Consequently, inadequate mixing can lead to significant localized variations in all physical and chemical parameters during cultures of algae (Borowitzka 2016).…”
Section: Introductionmentioning
confidence: 99%